Funkcja edukacyjna biblioteki uczelnianej na przykładzie Biblioteki Politechniki Lubelskiej - Matczuk, Ewa (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The article presents the training offer of Lublin University of Technology Library in the field of information literacy education. It also identifies the role of academic libraries in supporting information literacy at every stage of life through the discussion of services targeted at different users.